Sodium-doped copper target material and preparation method thereof
By using ball milling and vacuum hot pressing sintering methods in the preparation of sodium-doped copper targets, the problems of low doping uniformity and density are solved, and high density and uniform sodium-doped copper targets are achieved, which improves the performance of the film.
Patent Information
- Application Number
- CN202411842089.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
In the existing preparation methods for sodium-doped copper targets, doping uniformity is poor, density is not high, and the surface of the target material is rough.
Sodium-doped copper target was prepared by mixing the copper powder and Na-containing powder, pre-pressing it in the mold and then sintering it in a vacuum. During the ball milling process, polyurethane ball milling tanks and zirconium balls are used to ensure the uniformity of the mixture; vacuum hot pressing sintering is carried out under high temperature and high pressure to ensure the density and purity of the material.
The high density and uniformity of sodium-doped copper targets are achieved, the roughness of the target surface is reduced, and the low resistance of subsequent films and the uniformity of the film layer are improved.
Smart Images

Figure CN119710585A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of target material preparation, and more specifically, relates to a sodium-doped copper target material and a preparation method thereof. Background Art
[0002] Copper target is a material used in physical vapor deposition (PVD) technologies such as magnetron sputtering, and is mainly used to produce thin films for electronic devices such as semiconductors, displays, and solar cells.
[0003] Sodium-doped copper targets refer to copper targets with trace amounts of sodium added to improve the physical and chemical properties of the copper targets. In the semiconductor field, sodium-doped copper targets can be used to manufacture high-precision circuit boards, and their electrical conductivity helps improve the transmission efficiency of circuits and the stability of signals. In the field of solar cells, sodium-doped copper targets can be used as electrode materials, and their good thermal stability helps improve the conversion efficiency and service life of solar cells. In addition, sodium-doped copper targets also have lower resistivity and higher reflectivity, which make them potentially useful in optoelectronic devices. With the development of new energy technologies, the application scope of sodium-doped copper targets is expected to expand further.
[0004] In the prior art, there are still some problems in the preparation method of sodium-doped copper targets that need to be solved, such as poor doping uniformity, low density, and rough target surface that may appear during use. Summary of the invention
[0005] The object of the present invention is to provide a sodium-doped copper target and a preparation method thereof, so as to solve at least one of the above problems existing in the prior art.
[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a sodium-doped copper target comprises the following steps: (1) mixing copper powder and Na-containing powder, ball-milling, and then homogenizing to obtain a raw material mixture; (2) The raw material mixture is placed in a mold, pre-pressed, and then vacuum hot-pressed and sintered to obtain a sodium-doped copper target.
[0007] Furthermore, in the raw material mixture obtained in step (1), the amount of Na element added is 4-5wt%.
[0008] Furthermore, the Na-containing powder is at least one of sodium selenite, sodium fluoride and sodium hydroxide.
[0009] Furthermore, the purity of the copper powder is ≥4N.
[0010] Furthermore, the particle size of the copper powder and the Na-containing powder is ≤45 microns.
[0011] Furthermore, in step (1), the mixed powder is ball-milled and homogenized under a protective gas atmosphere. Preferably, the protective atmosphere is nitrogen or an inert gas.
[0012] Furthermore, a polyurethane ball mill is used in the ball milling process to effectively avoid material contamination.
[0013] Furthermore, zirconium balls are added as grinding balls. Preferably, the ball-to-material mass ratio is 1:1.
[0014] Furthermore, the ball milling time is 4 to 6 h; During the ball milling process, the selection of the ball-to-material ratio has an important influence on the ball milling efficiency and the uniformity of the mixture. The present invention further preferably uses zirconium balls with diameters of 10 mm, 15 mm, and 20 mm; the mass ratio of 10 mm, 15 mm, and 20 mm zirconium balls is 1:1:1. Ensure that the mixed powder is fully ground and mixed during the ball milling process, while avoiding excessive ball milling that leads to excessive crushing of the material. By precisely controlling the zirconium ball diameter, ball-to-material ratio, and ball milling time, a raw material mixture with uniform particle size distribution and no obvious agglomeration can be obtained, which is conducive to subsequent vacuum hot pressing sintering.
[0015] Furthermore, the ball mill is placed in a homogenizer for homogenization; during the homogenization process, the mixture in the ball mill is subjected to strong shear and impact forces, which helps to further refine the powder particles and improve the uniformity of the mixture. The speed and processing time of the homogenizer need to be controlled to ensure that the mixture reaches an ideal dispersion state while avoiding particle breakage caused by excessive shearing. The present invention further preferably has a homogenization time of 2 to 3 hours.
[0016] Further, after ball milling, a first screening is performed using an 8-mesh sieve, and the mixed powder passing through the sieve is homogenized.
[0017] Furthermore, after homogenization, a second screening is performed using an 8-mesh sieve, and the mixed powder passing through the sieve is the raw material mixture.
[0018] Furthermore, step (2) mold pre-pressing process: During the mold filling process, the air temperature is maintained at 20~30℃ and the air humidity is maintained at 40~50%. The temperature and humidity control is increased to make the powder dry during the filling process and the powder does not agglomerate; Lay graphite paper on the inner wall of the mold; The mold is a graphite mold; The preloading pressure is 5~10MPa.
[0019] In the pre-pressing process of the present invention, the use of graphite paper can effectively prevent the raw material mixture from directly contacting the mold, thereby reducing pollution and improving the purity of the target material.
[0020] Graphite molds have good thermal stability and can withstand the high temperatures during the subsequent hot pressing and sintering process. At the same time, the thermal conductivity of graphite helps to evenly distribute the temperature during the hot pressing process.
[0021] The setting of the pre-pressing pressure of the present invention can ensure that the raw material mixture has a certain initial density before entering the vacuum hot pressing sintering stage, and the control of the pre-pressing speed can prevent the raw material mixture from generating cracks or unevenness under rapid compression. Through the pre-pressing step, a uniform and stable raw material mixture is provided for subsequent hot pressing sintering, thereby improving the quality and performance of the final sodium-doped copper target.
[0022] Furthermore, step (2) vacuum hot pressing sintering process: When the vacuum degree in the furnace reaches 5~10Pa, start heating, raise the temperature to 650~700℃ at 5~10℃ / min, and keep warm for 90~100min; Among them: after keeping warm for 30 to 40 minutes, start to pressurize to 35 to 40 MPa, and then keep warm and maintain pressure, and the keeping warm and pressure time is 70 to 90 minutes.
[0023] After the hot pressing is completed, the pressure is released and the furnace is cooled.
[0024] The present invention performs hot pressing sintering in a vacuum environment to ensure the purity and uniformity of the target material.
[0025] During the vacuum hot pressing sintering process, the heating rate set by the present invention helps to prevent thermal stress from being generated inside the raw material mixture and avoid cracks. During the heat preservation stage, the raw material mixture is allowed to fully react to form a uniform microstructure. After the raw material mixture is kept warm for a period of time, a pressurization process is performed to ensure that the raw material mixture can be fully densified at high temperature to form a high-quality sodium-doped copper target. The heat preservation and pressure holding stage ensures that the material is fully densified under high temperature and pressure while maintaining the uniformity of the material.
[0026] The invention also discloses a sodium-doped copper target material obtained by the above preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects: The present invention mixes copper powder and Na-containing powder and ball mills to ensure that copper and sodium powders can be fully mixed to form a uniform raw material mixture. During the ball milling process, the ball milling medium generates strong impact and shear force in the ball milling tank, breaks the powder particles, increases the contact area between the powders, and promotes mixing and homogenization. Before hot pressing and sintering, the present invention puts the raw material mixture into a mold and applies a certain pressure to form a relatively dense preform. It is helpful to reduce the volume shrinkage of the material during the hot pressing and sintering process, and improve the density and uniformity of the sintered body. Finally, hot pressing and sintering are carried out in a vacuum environment. The vacuum environment can remove oxides and other volatile impurities that may be generated during the sintering process, and improve the purity of the material. Hot pressing can provide enough energy to diffuse and combine between the powder particles to form a dense sintered body. During the hot pressing and sintering process, the sodium element in the sodium-doped copper target material will be evenly distributed in the copper matrix, thereby achieving the purpose of doping.
[0028] The invention adopts a polyurethane ball milling tank, which can effectively avoid the pollution of materials, and adopts a ball milling and tumbling homogenization technology to make the copper-doped sodium selenite powder components more uniform.
[0029] The target material prepared by the present invention has a high relative density of more than 90% and a uniform component. The film prepared by the later sputtering exhibits excellent properties such as uniform film layer and low resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 This is the EDS image of the copper-doped sodium selenite powder after homogenization in step (2) of comparative example 1; Figure 2 This is the EDS image of the copper-doped sodium selenite powder after homogenization in step (2) of Example 1; Figure 3 This is the EDS image of the target material obtained in step (2) of comparative example 1; Figure 4 This is the EDS image of the target material obtained in step (2) of Example 1. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0032] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0034] It should be noted in this embodiment that: Density detection: The specific detection is carried out using the volume method principle.
[0035] Purity detection is carried out using a GDMS instrument (full name: glow discharge mass spectrometry).
[0036] The components were detected using an ICP-OES (inductively coupled plasma-optical emission spectrometer).
[0037] Comparative Example 1 (1) Take copper powder with a purity of 4N and sodium selenite powder with a purity of 3.5N. The particle sizes of the copper powder and sodium selenite powder are both below 45 mm, and the water content of the sodium selenite powder is ≤0.2ppm.
[0038] Prepare a polyurethane ball mill and pass argon gas into the polyurethane ball mill to expel the air in the ball mill. Weigh copper powder and sodium selenite at a mass ratio of 87.47wt%:12.53wt% and put them into a 5L polyurethane ball mill. Then put zirconium balls at a ball-to-material weight ratio of 1:1, where the mass ratio of zirconium balls with a diameter of φ5mm and a diameter of φ10mm is 4:1.
[0039] Argon gas was passed into the polyurethane ball mill to further expel the air in the ball mill, and then the ball mill was sealed and ball milling began. After ball milling for 6 hours, it was left to stand for 1 hour, and the copper-doped sodium selenite powder was sieved out with an 8-mesh stainless steel sieve.
[0040] (2) Prepare a glove box filled with an inert gas atmosphere to maintain the water content in the box less than 1ppm and the oxygen content less than 10ppm. Pass argon gas into the polyurethane ball mill to exhaust the air in the ball mill. Operate in the glove box: Place copper-doped sodium selenite powder into a 5L polyurethane ball mill, and then add zirconium balls at a ball-to-material mass ratio of 1:1, including: all zirconium balls with a diameter of φ15mm, a total of 50 balls.
[0041] The polyurethane ball mill was passed with argon to further expel the air in the ball mill, and then the ball mill was sealed and placed in a tumbling homogenizer for homogenization for 1 hour, and then left to stand for 1 hour. The copper-doped sodium selenite powder was sieved out with an 8-mesh stainless steel screen, and placed in a PP barrel and filled with argon for 30-40 minutes at 2-3 L / min to expel the air in the PP barrel and seal it.
[0042] (3) Lay graphite paper with a thickness of 0.38 mm on the inner wall of the graphite mold, and then put copper-doped sodium selenite powder into the graphite mold with graphite paper. The pre-pressing pressure is 10 MPa to expel the air in the graphite mold. Keep it for 3 minutes to obtain a green body.
[0043] Close the furnace door, evacuate until the vacuum degree in the furnace reaches 10Pa, start heating, raise the temperature to 650℃ at 10℃ / min, and keep warm for 90min. The specific steps of the insulation are as follows: start pressurizing after keeping warm for 30min, and then keep warm and pressurize. The insulation and pressure keeping pressure is 40MPa, and the insulation and pressure keeping time is 60min. After the insulation and pressure keeping is completed, close the hydraulic station, drop the temperature to 300℃, fill with nitrogen for cooling, and obtain the sodium-doped copper target after demolding.
[0044] The target obtained in this comparative example has sodium selenite agglomeration on the surface after processing, surface color difference, and overall unevenness of sodium selenite. The density is about 87% measured by volume method. Figure 3 As shown, EDS analysis shows that the overall distribution of the target powder is uneven.
[0045] Example 1 (1) Take copper powder with a purity of 4N and sodium selenite powder with a purity of 3.5N. The particle sizes of the copper powder and sodium selenite powder are both below 45 mm, and the water content of the sodium selenite powder is ≤0.2ppm.
[0046] Prepare a glove box filled with an inert gas atmosphere to maintain the water content in the box less than 1 ppm and the oxygen content less than 10 ppm.
[0047] Prepare a polyurethane ball mill and pass argon gas into the polyurethane ball mill to expel the air in the ball mill. Weigh copper powder and sodium nitrite in a glove box at a mass ratio of 87.47wt%:12.53wt%, put them into a 5L polyurethane ball mill, and then put zirconium balls in a ball-to-material ratio of 1:1, where the mass ratio of zirconium balls with a diameter of φ10mm, φ15mm, and φ20mm is 1:1:1.
[0048] Argon gas was passed into the polyurethane ball mill to further expel the air in the ball mill, and then the ball mill was sealed and ball milling began. After ball milling for 10 hours, it was left to stand for 1 hour, and the copper-doped sodium selenite powder was sieved out with an 8-mesh stainless steel sieve.
[0049] (2) Prepare a glove box filled with an inert gas atmosphere to maintain the water content in the box less than 1ppm and the oxygen content less than 10ppm. Pass argon gas into the polyurethane ball mill to exhaust the air in the ball mill. Operate in the glove box: Place copper-doped sodium selenite powder into a 5L polyurethane ball mill, and then add zirconium balls at a ball-to-material ratio of 1:1, including: all zirconium balls with a diameter of φ15mm, a total of 50 balls.
[0050] The polyurethane ball mill was passed with argon to further expel the air in the ball mill, and then the ball mill was sealed and placed in a tumbling homogenizer for homogenization for 1 hour, and then left to stand for 1 to 2 hours. The copper-doped sodium selenite powder was sieved out with an 8-mesh stainless steel screen, and placed in a PP barrel and filled with argon for 30 to 40 minutes at 2 to 3 L / min to expel the air in the PP barrel and seal it.
[0051] (3) During the molding process, the room temperature and humidity were controlled at 25°C and 50%, respectively. A graphite paper with a thickness of 0.38 mm was laid on the inner wall of the graphite mold. Then, copper-doped sodium selenite powder was placed in the graphite mold with the graphite paper. The pre-pressing pressure was 5 MPa to expel the air in the graphite mold. The pre-pressing pressure was maintained for 3 to 5 minutes to obtain a green body.
[0052] Close the furnace door, evacuate until the vacuum degree in the furnace reaches 5~10Pa, start heating, raise the temperature to 700℃ at 5~10℃ / min, and keep warm for 100min. The specific steps of the insulation are as follows: start pressurizing after keeping warm for 30min, and then keep warm and pressurize. The insulation and pressure keeping pressure is 40MPa, and the insulation and pressure keeping time is 70min. After the insulation and pressure keeping is completed, close the hydraulic station, drop the temperature to 300℃, fill with nitrogen for cooling, and obtain the sodium-doped copper target after demolding.
[0053] The target material obtained in this embodiment has no color difference on the surface after processing, and the density is measured by volume method to reach 95%. EDS analysis shows that the overall distribution of the target material powder is uniform.
[0054] The component contents of Comparative Example 1 and Comparative Example 1 were detected, and the powders in the upper, middle and lower parts of the homogenizing barrel were sampled respectively after homogenization, wherein the contents of Cu and Na2SeO3 were as follows: The Cu contents in Comparative Example 1 are 87wt%, 86wt%, and 86.5wt% respectively; The Cu contents in Example 1 are 87.4 wt%, 87.6 wt%, and 87.5 wt% respectively; In Comparative Example 1, the contents of Na2SeO3 were 13wt%, 14wt%, and 13.5wt% respectively; The contents of Na2SeO3 in Example 1 are 12.6wt%, 12.4wt% and 12.5wt% respectively.
[0055] By comparing the components, the component content of Comparative Example 1 is relatively poor, and Example 1 is closer to the actual ingredient ratio, which shows that the powder obtained by the ball milling and homogenization process of this example has better uniformity.
[0056] The copper-doped sodium selenite powder obtained after homogenization of Comparative Example 1 and Example 1 was subjected to EDS detection to verify the microscopic uniformity. Figure 1 and2 As shown, the ratio of zirconium balls and the ball milling homogenization time affect the uniformity of the powder. Under EDS comparison, the powder uniformity of Example 1 is poor and powder agglomeration occurs. The powder of Example 1 is evenly distributed as a whole and has better uniformity.
[0057] The target materials obtained after homogenization of Comparative Example 1 and Example 1 were subjected to EDS detection to verify the microscopic uniformity. Figure 3 and 4 As shown, in comparison, the powder of comparative example 1 has poor uniformity after hot pressing, and the overall distribution is uneven. The target material of embodiment 1 is evenly distributed as a whole, and has better uniformity.
[0058] The target materials obtained in Comparative Example 1 and Example 1 were observed and their densities were detected. The density of the target materials was verified by sampling three locations as follows: The relative densities of comparative example 1 are: 87%, 89%, 89% respectively; The relative densities of Example 1 are respectively: 96%, 93%, and 95%.
[0059] The target material obtained in Comparative Example 1 has a poor overall surface appearance and many surface pits, while the target material obtained in Example 1 has a good overall surface appearance and a smooth surface.
[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of the present invention.
Claims
1. A method for preparing a sodium-doped copper target, characterized in that: The following steps are involved: (1) mixing copper powder and Na-containing powder, ball-milling, and then homogenizing to obtain a raw material mixture; (2) The raw material mixture is placed in a mold, pre-pressed, and then vacuum hot-pressed and sintered to obtain a sodium-doped copper target.
2. The preparation method according to claim 1, characterized in that In the raw material mixture obtained in step (1), the amount of Na element added is 4-5wt%.
3. The preparation method according to claim 1 or 2, characterized in that: The Na-containing powder is at least one of sodium selenite, sodium fluoride and sodium hydroxide; The purity of the copper powder is ≥4N; The particle size of the copper powder and the Na-containing powder is ≤45 microns.
4. The preparation method according to claim 1, characterized in that: In step (1), the mixed powder is ball-milled and homogenized under a protective gas atmosphere; The protective atmosphere is nitrogen or an inert gas.
5. The preparation method according to claim 1 or 4, characterized in that: During the ball milling process, a polyurethane ball mill was used; zirconium balls were added; the ball-to-material mass ratio was 1~2:1~2; the ball milling time was 4~6h; Place the ball mill into a homogenizer for homogenization; The homogenization time is 4~6h.
6. The preparation method according to claim 5, characterized in that: Zirconium balls with diameters of 10mm, 15mm, and 20mm are used; the mass ratio of 10mm, 15mm, and 20mm zirconium balls is 1:1:
1.
7. The preparation method according to claim 1 or 4, characterized in that: After ball milling, an 8-mesh screen was used for the first screening, and the mixed powder passing through the screen was homogenized; After homogenization, a second screening is performed using an 8-mesh sieve, and the mixed powder passing through the sieve is the raw material mixture.
8. The preparation method according to claim 1, characterized in that: Step (2) Die pre-pressing process: During the molding process, the air temperature is maintained at 20~30℃ and the air humidity is maintained at 40~50%; Lay graphite paper on the inner wall of the mold; The mold is a graphite mold; The preloading pressure is 5~10MPa.
9. The preparation method according to claim 1, characterized in that: Step (2) Vacuum hot pressing sintering process: When the vacuum degree in the furnace reaches 5~10Pa, start heating, raise the temperature to 650~700℃ at 5~10℃ / min, and keep warm for 90~100min; Among them: after keeping warm for 30 to 40 minutes, start to pressurize to 35 to 40 MPa, and then keep warm and maintain pressure, and the keeping warm and pressure time is 70 to 90 minutes.
10. The sodium-doped copper target obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Manufacturing Method Of Composite Copper-gallium Alloy Sodium Element Target
CN106282941A
Preparation method of copper-doped zinc telluride target material
CN113372117A
Sputtering target and manufacturing method thereof
JP2015028213A
Sputtering target and method for producing same
US20140034491A1